Causes of deafness in the Punjab region of Pakistan and the role of consanguinity. (April 2017) - Ullah, S.; Aslamkhan, M.; Ali, A.; Idrees, M.
Highlights: Punjab is a mixture of diverse ethnicities with unique familial and social characteristics. Rate of consanguinity and their potential role in increasing deafness in Punjabi population. Cousin marriages are more common in district Chakwal, while lowest was observed in Rajanpur. Highest congenital deafness was observed in Rajput families (15.6%) while lowest in Chema (3.9%) and Jawar (3.9%). We found that consanguinity is quite common that leading to genetic abnormalities.